The Legal Ideal of Pancasila in the Perspective of Postmodernism - Hyronimus Rhiti; Yosephin Jasmine Safitri (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
The legal ideal of Pancasila, as the foundation of the Indonesian state, has long been regarded as a stable and universal ideology. However, with the development of postmodern thought, which emphasizes relativism, pluralism, and the deconstruction of grand narratives, the relevance of Pancasila's legal ideal within the postmodern context requires further exploration. This study aims to examine whether Pancasila's legal ideal remains relevant from a postmodern perspective and how postmodernism may influence the application of Pancasila's legal principles in Indonesia. This research uses a normative method with a philosophical approach, which is prescriptive in nature, to explore postmodern thoughts related to law, ideology, and the state. The analysis technique used is deductive, starting from postmodern theories and applying them to the context of Pancasila law. The findings suggest that, from a postmodern perspective, the legal ideal of Pancasila should not be seen as a rigid and singular legal system. Instead, Pancasila can be understood as a flexible principle, open to change, and accommodating diverse viewpoints within Indonesia's pluralistic society. However, a deeper understanding is required on how the values of Pancasila can be dynamically interpreted, in line with the demands of the times and the challenges of globalization faced by Indonesia. This study concludes that Pancasila's legal ideal remains relevant, but must be adapted to the ongoing social and cultural developments